Adapting computer-based micro learning to enhance student retention of SQL key terms / Noor Awawdeh, Noornina Dahlan and Azira Ab Aziz - Awawdeh, Noor; Dahlan, Noornina; Ab Aziz, Azira (Universiti Teknologi MARA Melaka Kampus Jasin, 2021)
The focus in this study is to explore the methods of using computer-based micro learning to enhance student retention in Structured Query Language (SQL) key terms. One of the primary issues in teaching technical courses is a difficulty for students to recall and explain terminologies. It is one of the fundamental skills when learning technical courses. Educators introduce many techniques or methods to reduce students’ difficulties such as implementing a micro learning concept. The concept of computer based micro learning encompasses a modern approach to learning, based on short, concise lessons delivered to the learners. Micro learning allows knowledge and information to be divided into small “chunks”. Method: This study conducts a survey after each lesson to compare the number of terminology that students can recall or explain. First, students are given a lesson without adding a micro learning revision. Then, students receive additional micro learning revision to help them to recall. Results: Using the evidence from the questionnaire, the six cases are classified into two categories that have a little improvement and no improvement. Most cases demonstrate improvement when asked to recall SQL terminology. Summary: the study finds the retention and understanding level increases in comparison with traditional methods. In assessing student performance, this paper emphasizes the use of available technology to support classroom activities. The paper considers the implications for the teaching approach and student learning.